3D image-based adapted high-dose-rate brachytherapy in cervical cancer with and without interstitial needles: measurement of applicator shift between imaging and dose delivery - Karlsson, Leif; Thunberg, Per; With, Anders; Mordhorst, Louise Bohr; Persliden, Jan (Journal of Contemporary Brachytherapy, 2017)
Purpose: Using 3D image-guided adaptive brachytherapy for cervical cancer treatment, it often means that patients are transported and moved during the treatment procedure. The purpose of this study was to determine the intra-fractional longitudinal applicator shift in relation to the high risk clinical target volume (HR-CTV) by comparing geometries at imaging and dose delivery for patients with and without needles. Material and methods : Measurements were performed in 33 patients (71 fractions), where 25 fractions were without and 46 were with interstitial needles. Gold markers were placed in the lower part of the cervix as a surrogate for HR-CTV, enabling distance measurements between HR-CTV and the ring applicator. Shifts of the applicator relative to the markers were determined using planning computed tomography (CT) images used for planning, and the radiographs obtained at dose delivery. Differences in the physical D90 for HR-CTV due to applicator shifts were simulated individually in the treatment planning system to provide the relative dose variation. Results : The maximum distances of the applicator shifts, in relation to the markers, were 3.6 mm (caudal), and –2.5 mm (cranial). There was a significant displacement of –0.7 mm (SD = 0.9 mm) without needles, while with needles there was no significant shift. The relative dose variation showed a significant increase in D90 HR-CTV of 1.6% (SD = 2.6%) when not using needles, and no significant dose variation was found when using needles. Conclusions : The results from this study showed that there was a small longitudinal displacement of the ring applicator and a significant difference in displacement between using interstitial needles or not.